PRONOMINA DALAM BAHASA MELAYU MANADO - Asri M. Nur Hidayah (Balai Bahasa Sulawesi Selatan, 2013)
This research aimed to describe pronouns in Manado Malay. The data consists of spoken languages thatgathered from native speakers and written ones that taken from the Bible—Joseph and Jonas, Manado- MalayDictionary, the adolescent's short stories in Manado Malay, and populer songs in Manado Malay. This researchmethod by using descriptive.The data were collected by listening and writing techniques. The data analyzedwith structural analysis. The result shown that there were three pronouns; personal pronoun, demonstrativepronoun, andpossessive pronouns called as independent pronouns,characteristic of pronoun is interchangeable,another characteristic possessive pronouns in front of noun. Generally, those pronouns function as subjects andadverbs. AbstrakPenelitian ini bertujuan untuk mendeskripsikan pronomina dalam bahasa Melayu Manado. Data diperolehdari penutur asli, terjemahan Alkitab ke dalam bahasa Melayu Manado, kamus Melayu Manado, lagu populerdalam bahasa Melayu Manado. Data dikumpulkan dengan teknik simak dan teknik catat. Data dianalisis denganmenggunakan analisis struktural dengan pendekatan kualitatif. Hasil penelitian ini memperlihatkan ada tigajenis pronomina, yaitu 1) pronomina persona, 2) pronomina kepemilikan, 3) pronomina penunjuk umum.Berdasar bentuknya, pronomina bahasa Melayu Manado merupakan pronomina mandiri. Ditinjau dari ciricirinya,pronomina bahasa Melayu Manado acuannya berpindah-pindah, ciri lainnya pronomina kepemilikanselalu berada di sebelah depan nomina. Ditinjau dari fungsinya dalam kalimat, pronomina bahasa MelayuManado sebagian besar menduduki fungsi subjek dan keterangan dalam kalimat.